2018
DOI: 10.1038/s41467-018-07031-1
|View full text |Cite
|
Sign up to set email alerts
|

Direct oxygen isotope effect identifies the rate-determining step of electrocatalytic OER at an oxidic surface

Abstract: Understanding the mechanism of water oxidation to dioxygen represents the bottleneck towards the design of efficient energy storage schemes based on water splitting. The investigation of kinetic isotope effects has long been established for mechanistic studies of various such reactions. However, so far natural isotope abundance determination of O2 produced at solid electrode surfaces has not been applied. Here, we demonstrate that such measurements are possible. Moreover, they are experimentally simple and suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 68 publications
4
61
0
Order By: Relevance
“…The authors of cited work showed that the rate‐determining step of the OO bond formation is the nucleophilic water attack on a ferryl unit rather than a direct coupling of two ferryl units. Our computational data from the present and previous work are in a perfect agreement with these findings [20].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The authors of cited work showed that the rate‐determining step of the OO bond formation is the nucleophilic water attack on a ferryl unit rather than a direct coupling of two ferryl units. Our computational data from the present and previous work are in a perfect agreement with these findings [20].…”
Section: Resultssupporting
confidence: 92%
“…The same mechanism for water oxidation on iron oxide electrode was identified by means of direct isotope effect in a recent work by Haschke et al [20]. The authors of cited work showed that the rate‐determining step of the OO bond formation is the nucleophilic water attack on a ferryl unit rather than a direct coupling of two ferryl units.…”
Section: Resultsmentioning
confidence: 54%
“…This hypothetical reaction mechanism was later supported by isotope labelling experiments and analyzing the O 2 products using isotope ratio mass spectroscopy. 203 With the combination of photoinduced absorption spectroscopy (PIA) and transient photocurrent spectroscopy (TPS), a first-order reaction was actually observed by Durrant et al when the illumination intensity was weak (Fig. 10c).…”
Section: Mechanistic Advances For Heterogeneous Wocsmentioning
confidence: 82%
“…18), and the average Ru-N bond distance is obtained as 2.02 Å, which is in good agreement with the EXAFS fitting value. Generally, the conventional OER in an acidic medium involves four concerted proton–electron transfer steps on surface metal sites, generating three different intermediate adsorbates: OH * , O * , and OOH * (the asterisk denotes the adsorption site) 40 . As the Ru site is believed to be the catalytically active center, Fig.…”
Section: Resultsmentioning
confidence: 99%